Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1063/1.5012093
|View full text |Cite
|
Sign up to set email alerts
|

Observation of radially inward turbulent particle flux in ETG dominated plasma of LVPD

Abstract: Radially inward turbulent particle flux is observed in the core region of target plasma of Large Volume Plasma Device(LVPD)where electron temperature driven turbulence condition satisfied region satisfy conditions for ETG turbulence, i.e. threshold condition, η e = L ne /L Te > 2/3 , where density scale length, L ne ∼ 300cm and temerature scale length, L Te ∼ 50cm[S.K. Mattoo et al., Phys. Rev. Lett., 108, 255007(2012) 1 ]. The measured flux is dominantly electrostatic (Γ es ≈ 10 5 Γ em ) although the nature o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Now recall the expression for electrostatic electron flux from Ref [8]. In figure 11, we have made an attempt to estimate the experimentally observed particle flux due to electron and ion parallel motion, It was observed that the average electron and ion flux contribution differ significantly.…”
Section: A Quasilinear Theory For Electromagnetic Particle Fluxmentioning
confidence: 99%
See 4 more Smart Citations
“…Now recall the expression for electrostatic electron flux from Ref [8]. In figure 11, we have made an attempt to estimate the experimentally observed particle flux due to electron and ion parallel motion, It was observed that the average electron and ion flux contribution differ significantly.…”
Section: A Quasilinear Theory For Electromagnetic Particle Fluxmentioning
confidence: 99%
“…In figure 12, the electromagnetic fluctuations driven radial electron flux is measured during the steady state period between (6)(7)(8)…”
Section: B Radial Profiles Of Ion and Electron Fluxes And Comparisonmentioning
confidence: 99%
See 3 more Smart Citations